2014
DOI: 10.1177/1941738114524910
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Landing Mechanics in Patients Following Anterior Cruciate Ligament Reconstruction When Wearing an Extension Constraint Knee Brace

Abstract: Background:Anterior cruciate ligament (ACL) reconstruction is associated with a high incidence of second tears (graft tears and contralateral ACL tears). These secondary tears have been attributed to asymmetrical lower extremity mechanics. Knee bracing is one potential intervention that can be used during rehabilitation that has the potential to normalize lower extremity asymmetry; however, little is known about the effect of bracing on movement asymmetry in patients following ACL reconstruction.Hypothesis:Wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Previous studies have shown that knee braces may improve functional performance during tasks such as single limb balance in individuals with ACL injuries [12,13]. Butler et al [14] also showed changes in landing mechanics in patients following ACL reconstruction while wearing a brace. To date no study has determined the size and nature of the effects of using proprioceptive knee bracing during more dynamic tasks on 3D knee mechanics.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have shown that knee braces may improve functional performance during tasks such as single limb balance in individuals with ACL injuries [12,13]. Butler et al [14] also showed changes in landing mechanics in patients following ACL reconstruction while wearing a brace. To date no study has determined the size and nature of the effects of using proprioceptive knee bracing during more dynamic tasks on 3D knee mechanics.…”
Section: Introductionmentioning
confidence: 98%
“…Asymmetries in loading and movement patterns between limbs can be present up to 2 years after reconstruction contributing to increased risk for ACL re‐injury to both the surgical and non‐surgical limb . ACLR patients have a tendency to land with increased knee abduction moments and knee extension, as well as decreased peak knee flexion moments, and vertical ground reaction forces .…”
mentioning
confidence: 99%
“… 16 , 23 , 35 There is evidence that brace wear may improve movement mechanics during walking and running by increasing knee flexion 8 , 41 and during cutting by increasing knee flexion velocity at initial contact. 8 , 9 Additional research has shown that braces improve jumping mechanics such as bilateral landing symmetry 6 and vertical jump height. 33 One study found that hop distance symmetry improved with time and a braced condition, which suggests that both time and bracing may not only improve physical performance but also help prevent additional injury.…”
Section: Discussionmentioning
confidence: 99%